The characteristic of the component body composition of athletes involved in game-based and cyclic kinds of sports - S. V. Gudimov; A. N. Shkrebko; I. A. Osetrov; I. E. Pleshcheev; M. A. Kuznetsov (National Electronic Information Consortium (NEICON), 2021)
Objective: to determine a component body composition of students specializing in volleyball and athletics and to conduct a comparative analysis of the results.Materials and methods: the study was conducted at the Department of physical training and sports at the Yaroslavl State Medical University of the Ministry of Health of the Russian Federation. The study included students from different groups of physical training: volleyball (10 men and 10 women), athletics (10 women) (experimental groups), and firstyear students that attended physical training classes (14 men and 16 women) (control group).Results: significant differences were revealed between the anthropometric measurements in the experimental groups of the studied women and between the results of anthropometric measurements in the female volleyball players, female athletes, and students from the control group. Significant differences were revealed in the component body composition of the studied women from the experimental and control groups. The analysis of the results of anthropometric measurements in the experimental and control groups of men did not reveal any significant differences between the parameters. Bioimpedancemetry revealed significant differences in the composition of the internal milieu of volleyball players in comparison with the control group.Conclusions: 1. differences were revealed in the component composition of the body of female athletes involved in gamebased and cyclic kinds of sport as well as in the parameters of bioimpedance of female volleyball players and the control group. Female volleyball players had higher parameters of total body fluids, intracellular and extracellular fluids, fatfree, fat, and active cell mass in comparison with female light athletes and the control group. The differences in the obtained results were more significant in the experimental groups. 2. Bioimpendance analysis of men showed significant differences in the component body composition of volleyball players in comparison with untrained students. The parameters of total body fluids, fatfree, fat, and active cell mass in sportsmen exceeded the same parameters in the control group. 3. Differences were established in the anthropometric parameters depending on the sportoriented specialization of female students. Female volleyball players had higher values of mass, length, body weight index, and body surface area, the circumferences of the pelvis, thighs, and wrists in comparison with the results obtained in female light athletes. Similar differences were revealed in the anthropometric parameters of female volleyball players and students from the control group. Significantly lower values of the body weight index, circumference of the chest and pelvis of female athletes were registered in comparison with students from the control group. Male volleyball players did not have significant differences in the anthropometric parameters. They tended to have an increase in the body mass, length and surface area of the body, circumference of the chest, thighs, and wrists.